Guide Vane (Gv) Governor Valve Plta Cikalong Unit 3 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hydro Power Plant or Pembangkit Listrik Tenaga Air (PLTA) is a power plant that uses renewable energy in the form of water. The Hydropower System converts the energy from flowing water into mechanical energy and then into electrical energy. Water flows from the rapid pipe (Penstock) to the waterwheel or turbine where the water will hit the blades causing the waterwheel or turbine to rotate.Guide Vane is part of the turbine which functions to control the water flowing to the turbine. The guide vane opening control is adjusted using the Hydraulic Power Unit. The greater the open percentage of the guide vane, the faster the turbine rotates. The smaller the open percentage of the guide vane, the slower the turbine rotates. The size of the open percentage of the guide vane is regulated by the governor.The governor is a system used to stabilize the turbine rotation at PT. Indonesia Power UP Saguling Sub Unit PLTA Cikalong. The governor control system is carried out using PLC and HMI.